2020
DOI: 10.4038/cjs.v49i3.7781
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic activity of fruit extracts of Sri Lankan endemic species <i>Garcinia quaesita</i> Pierre “Rathgoraka” and its isolated compound, garcinol

Abstract: The dried fruit of Garcinia quaesita Pierre (Clusiaceae), is a well-known endemic spice in Sri Lanka and has been documented in traditional medicine as an antidiabetic agent. The antihyperglycemic effect of cold water, hot water, water : acetone fruit extracts of G. quaesita and its isolated compound, garcinol in streptozotocin-induced diabetic rats was studied. The percentage improvements of glucose tolerance upon total area under the oral glucose tolerance curve in cold water, hot water and water:acetone ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…This might be due to the presence of antidiabetic and antioxidant compounds and inhibitors of carbohydrate digestion enzymes. These results corroborate with those of other in vitro studies and the antihyperglycemic effect of hexane and ethyl acetate extracts would be due to the availability of a higher number of antidiabetic compounds, such as mahanimbine, isomahanimbine, koenimbidine, murrayacine koenimbine, myricetin, diallyl sulfide, diallyl disulfide, diallyl trisulfide, piperine and garcinol, present in the selected plants and the synergism of the active phytoconstituents [16,[71][72][73][74][75][76] .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This might be due to the presence of antidiabetic and antioxidant compounds and inhibitors of carbohydrate digestion enzymes. These results corroborate with those of other in vitro studies and the antihyperglycemic effect of hexane and ethyl acetate extracts would be due to the availability of a higher number of antidiabetic compounds, such as mahanimbine, isomahanimbine, koenimbidine, murrayacine koenimbine, myricetin, diallyl sulfide, diallyl disulfide, diallyl trisulfide, piperine and garcinol, present in the selected plants and the synergism of the active phytoconstituents [16,[71][72][73][74][75][76] .…”
Section: Discussionsupporting
confidence: 89%
“…From the hexane extract, piperine and β-pinene have been recorded as the major isolated compounds, while β-caryophyllene has been isolated as the major compound from the ethyl acetate extract of PN seeds [46][47][48] . Garcinol has been recorded as the major isolated compound from the hexane extract of GQ fruits, as per literature reports [16] . Those characteristic peaks in the HPLC profile of hexane extract and ethyl acetate extract, therefore, may be due to the presence of either of the aforementioned compounds.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The plant extract of the A. sativum showed significant reduction in serum glucose, triglyceride and total cholesterol levels in diabetic rats (Eidi et al, 2006). There are few reports of antihyperglycemic and antihyperlipidemic effects of the G. quaesita in addition to a study on the antihyperglycemic activity of three selected extracts of the plant by our research group (Liyanagamage et al, 2020a). In addition, subchronic and acute toxicity profile of the hot water and water: acetone extract of above polyherbal mixture was also assessed and found that it is safe and effective for in vivo use (Liyanagamage et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In view of present investigation, antidiabetic effect of the plant mixture of selected polyherbal mixture may be due to potentiation of insulin synthesis and secretion from existing β cells in Langerhans. In addition, the antihyperglycemic effect of plant extract would be due to the reported availability of a higher number of antidiabetic compounds such as mahanimbine, isomahanimbine, koenimbidine, murrayacine and koenimbine, myricetin, diallyl sulfide, diallyl disulfide, diallyl trisulfide, piperine and garcinol present in the selected plants and the synergism of the active phytoconstituents (Dineshkumar et al, 2010;Handral et al, 2012;Padiya and Banerjee, 2013;Park et al, 2016;Jain et al, 2017;Radi´c et al, 2019;Liyanagamage et al, 2020a).…”
mentioning
confidence: 99%